Dialectal differences in the Production of English Vowels by Iraqi EFL Learners at University Level - Khalaf, Haneen Kareem; Mohammed, Fuad Jassim (Al-Adab Journal, 2022)
The present study investigates whether or not Iraqi EFL learners’ native dialect has an impact on their pronunciation of English monophthongs and to examine the reasons, behind the mispronunciation, they are expected to commit. To achieve this goal, sixty Iraqi participants speaking two Iraqi dialects i.e. qeltu and gilit dialect, were engaged to achieve a speech production task of the eleven English monophthongs in a /hvd/ context. The data were analyzed using PRAAT to extract first and second formant frequencies and as well as vowel duration for each vowel. Lobanov’s TELESUR G normalization algorithm (2006) was tracked to normalize F1 and F2 values. The normalized data were compared to results from Deterding (1997) and walls (1962). The results showed that Iraqi EFLLs produced the targeted vowels shorter than the control group represented by native English. In terms vowel quality, they produced lower and more fronted vowels than the control group. In addition, this study revealed that there are statistically significant cross-dialectal differences between gilit and qeltu-speaking EFLLs in the production English vowels. It is concluded that learners’ mother tongue has a role in their production of English vowels.